Effective Communication in Providing Medication Information and Patient Satisfaction: A Cross-sectional Survey in Denpasar - Noviyanti, Anak Agung Vivi; Antari, Ni Putu Udayana (Faculty of Pharmacy, Universitas Gadjah Mada, 2024)
Background: Pharmacy personnel should provide pharmaceutical care concerning the applicable standards. Furthermore, pharmacy management must consider patient satisfaction to ensure business continuity. Patient subjective factors strongly influence satisfaction. Meanwhile, patient perceptions of pharmaceutical services will change as their experience increases. The pharmacy must improve its services effectively and efficiently. Factors that affect patient satisfaction can assist pharmacies in improving service quality. Effective communication does not require additional resources to improve service quality. The same information can have different effects when presented in different ways.Objectives: Predict the domain of effective communication that influences patient satisfaction.Methods: The cross-sectional survey using a valid and reliable questionnaire was conducted in Denpasar. The research involved 100 pharmacy consumers and was taken with a convenience sampling technique. Data were analyzed descriptively, followed by a Chi-square test and multivariate analysis using logistic regression. The research involved four independent variables: pharmacy atmosphere, pharmacist performance, pharmaceutical technical competence, and interpersonal communication competence. Patient satisfaction is the dependent variable in this study. Results: Communication factors generally affect patient satisfaction in providing drug information. Among all the independent variables tested, interpersonal communication competence plays a significant role in predicting patient satisfaction with a p-value of 0.043 (Logistic regression with 95% confidence level).Conclusion: Patients who perceive pharmacists as having good interpersonal communication competence are 3,133 times more likely to be satisfied. Thus, pharmaceutical staff must train interpersonal communication skills to provide drug information to achieve patient satisfaction outcomes in pharmaceutical services.